Microsoft Excel 2019 Programming by Example with VBA, XML, and ASP - Korol, Julitta (Mercury Learning & Information, 2019)
A practical, how-to book on Excel programming, suitable for readers already proficient with the Excel user interface (UI). If you are looking to automate Excel routine tasks, this book will progressively introduce you to programming concepts via numerous illustrated hands-on exercises. --